Decreased Susceptibilities to Retapamulin, Mupirocin, and Chlorhexidine among Staphylococcus aureus Isolates Causing Skin and Soft Tissue Infections in Otherwise Healthy Children - McNeil, J. Chase; Hulten, Kristina G.; Kaplan, Sheldon L.; Mason, Edward O. (Antimicrobial agents and chemotherapy, 2014)
Topical antimicrobial and antiseptic agents are commonly used in the management of minor skin and soft tissue infections (SSTIs). Resistance to mupirocin has been documented in Staphylococcus aureus isolates causing SSTIs. Data are limited, however, on the prevalence of retapamulin resistance or tolerance to antiseptics. We sought to determine the prevalence of decreased susceptibility to retapamulin and mupirocin as well as the potential for decreased chlorhexidine susceptibility of S. aureus isolates from SSTIs in children. Two hundred isolates from patients with a single SSTI and 200 isolates from patients with ≥3 previous episodes from the years 2010 to 2012 were selected from an S. aureus surveillance study. Screening for retapamulin resistance was performed by the broth macrodilution method; mupirocin MICs were determined by Etest. PCR was performed for the presence of the smr gene associated with elevated MICs/minimum bactericidal concentrations (MBCs) to chlorhexidine. Among the isolates screened, 38 isolates (9.5%) exhibited retapamulin resistance, of which 22 (57.9%) were methicillin-resistant S. aureus (MRSA). Two isolates (0.5%) displayed cross-resistance to retapamulin and linezolid. Thirty-nine isolates (9.8%) were found to have mupirocin resistance. smr -positive S. aureus accounted for 14% of isolates. The proportion of smr -positive organisms increased during the study ( P = 0.005). The prevalence of in vitro resistance to topical antimicrobials among S. aureus isolates causing SSTI in healthy children in our community is almost 10%. Retapamulin resistance was associated with cross-resistance to linezolid in 0.5% of isolates. In addition, there was an increase in the proportion of smr -positive isolates. Further research including clinical correlations with these findings is warranted.